2006
DOI: 10.1111/j.1095-8649.2006.01235.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of river flow on larval growth and survival of Japanese seaperch Lateolabrax japonicus (Pisces) in the Chikugo River estuary, upper Ariake Bay

Abstract: The abundance and growth history of larval and juvenile Japanese seaperch Lateolabrax japonicus were investigated in the Chikugo River estuary, upper Ariake Bay, from 1990 to 2000. Growth during the larval period (up to 15 mm standard length, L S , the size at recruitment into the estuary) was backcalculated using sagittal otolith microstructures by the biological intercept method. Growth rates in length declined at body sizes >14 mm L S . High freshwater discharge through the Chikugo River was associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
41
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 29 publications
5
41
0
Order By: Relevance
“…Recent surveys have demonstrated that the biological and physical properties of the ETM, such as turbidity (Shoji et al, 2006a) and spatial and temporal distribution of chlorophyll and copepods (Okazaki et al, 2005;Ueda et al, 2004), fluctuate with the variability of freshwater discharge of the Chikugo River. Growth analyses using larval otolith microstructure have shown that temperature in the northern part of Ariake Bay and larval growth were high but the recruitment was poor in the years of high winter flow (Shoji et al, 2006b). This suggests that an increase in river flow may decrease Japanese seaperch recruitment in the Chikugo River estuary through a density-independent process, as reported in other estuarine dependent fishes (Turner and Chadwick, 1972;Hayman and Tyler, 1980;Crecco and Savoy, 1984;Rulifson and Manooch III, 1990;Strydom et al, 2002;Whitefield, 2005;Shoji et al, 2006b).…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…Recent surveys have demonstrated that the biological and physical properties of the ETM, such as turbidity (Shoji et al, 2006a) and spatial and temporal distribution of chlorophyll and copepods (Okazaki et al, 2005;Ueda et al, 2004), fluctuate with the variability of freshwater discharge of the Chikugo River. Growth analyses using larval otolith microstructure have shown that temperature in the northern part of Ariake Bay and larval growth were high but the recruitment was poor in the years of high winter flow (Shoji et al, 2006b). This suggests that an increase in river flow may decrease Japanese seaperch recruitment in the Chikugo River estuary through a density-independent process, as reported in other estuarine dependent fishes (Turner and Chadwick, 1972;Hayman and Tyler, 1980;Crecco and Savoy, 1984;Rulifson and Manooch III, 1990;Strydom et al, 2002;Whitefield, 2005;Shoji et al, 2006b).…”
mentioning
confidence: 66%
“…flow has been reported to be associated with high temperature (Shoji et al, 2006b). In addition, production of copepods-major prey organisms of the larval Japanese seaperch-in the upper Ariake Bay increased when the river flow increased (Okazaki et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recruitment variability indicated by age structure for king threadfin in a drytropical estuary was also shown to be positively related to freshwater flow (Halliday et al 2008). Not all studies, however, show positive linear effects of flow on (Deegan 1990, Rulifson & Manooch 1990, Sarre & Potter 2000, Shoji et al 2006. Flow is thought to have a positive influence on Japanese sea perch recruitment, except in years of very high flow (Shoji et al 2006), suggesting a domed relationship.…”
Section: Discussionmentioning
confidence: 92%
“…A number of studies have demonstrated a positive relationship between freshwater flow and recruitment variability of estuarine-dependent fish (Kimmerer et al 2001, North & Houde 2003, StauntonSmith et al 2004, Robins et al 2005 and invertebrates (Robins et al 2005). In other cases, however, high freshwater flows can have a detrimental effect on recruitment (Deegan 1990, Rulifson & Manooch 1990, Sarre & Potter 2000, Shoji et al 2006, with intermediate flows resulting in the highest recruitment success (Rulifson & Manooch 1990, Shoji et al 2006.…”
Section: Introductionmentioning
confidence: 99%